"Saving Science": narratives of scientific intolerance and cultural denial in Brazil - Echazú Böschmeier, Ana Gretel (Revista Mundaú, 2024)
This analysis aims to anthropologically explore the implications of anti-denialist reactions in contemporary Brazil. The rise of Bolsonaro’s government intensified concerns within the scientific community about the dangers of denialist discourses from extreme-right political positions (Szwako; Ratton, 2022). The Brazilian scientific community has actively countered these narratives to uphold science and public health (Echazú Böschemeier; Almeida, 2023b). However, some reactions were unexpected. This article examines the 2023 book “How Silly! Pseudosciences and Other Absurdities That Do Not Deserve to Be Taken Seriously” by virologist Natalia Pasternak and journalist Carlos Orsi, which had a divisive impact. While claiming to “Save Science” from far-right denialists, it attacks various traditions and cultures, labeling them as “pseudo-sciences.” I question this approach by analyzing the promotion of “scientific intolerance” — a dogmatic rejection of ideas outside hegemonic scientific norms — thus reinforcing conservatism, authoritarianism, and colonialism, while denying plural realities linked to health and culture.